2019
DOI: 10.1186/s12916-019-1460-0
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of primary screening using high-risk HPV DNA detection in the Dutch cervical cancer screening programme: a population-based cohort study

Abstract: BackgroundIn January 2017, the Dutch cervical cancer screening programme transitioned from cytomorphological to primary high-risk HPV (hrHPV) DNA screening, including the introduction of self-sampling, for women aged between 30 and 60 years. The Netherlands was the first country to switch to hrHPV screening at the national level. We investigated the health impact of this transition by comparing performance indicators from the new hrHPV-based programme with the previous cytology-based programme.MethodsWe obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
103
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 94 publications
(124 citation statements)
references
References 24 publications
12
103
3
Order By: Relevance
“…This is in line with the findings of randomised trials [2][3][4][5][6][7][8] and supports the higher sensitivity of HPV testing than cytology. Moreover, our finding is in line with previous implementation studies from England, 12 Netherlands, 28 Italy 21,22,25 and Finland. 18 In our study, the CIN3+ detection was 40-50% higher in the HPV than cytology group.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This is in line with the findings of randomised trials [2][3][4][5][6][7][8] and supports the higher sensitivity of HPV testing than cytology. Moreover, our finding is in line with previous implementation studies from England, 12 Netherlands, 28 Italy 21,22,25 and Finland. 18 In our study, the CIN3+ detection was 40-50% higher in the HPV than cytology group.…”
Section: Discussionsupporting
confidence: 93%
“…Our analysis also showed that HPV screening resulted in more colposcopy referrals at baseline than cytology, in line with previous results. 12,18,21,22,25,28 Excessive colposcopy referrals are problematic because they may lead to overtreatment of regressive CIN2, 4 and CIN treatment may increase the risk of pregnancy-related morbidity. 38 In our study, approximately 80% more women were referred to immediate colposcopy in the HPV than cytology group (3.8% versus 2.1%).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations